1978
DOI: 10.1172/jci109049
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Para-aminohippurate Secretion and Cellular Morphology in Rabbit Proximal Tubules

Abstract: A B S T R A C T Previous studies in the mammalian proximal tubule have suggested that para-aminohippurate (PAH) secretion is -threefold greater in the straight segment, or pars recta, than in the convoluted segment, or pars convoluta. However, the possibility that the site of maximal PAH secretion might be related better to particular tubule segments as identified by cell type had not been explored. In addition, the presence or absence of differences in PAH secretion between morphologically identical regions o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
46
0
1

Year Published

1978
1978
2013
2013

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(58 citation statements)
references
References 12 publications
11
46
0
1
Order By: Relevance
“…Many studies in different species, using different experimental techniques and designs, have addressed the sodium dependency ofthis active basolateral anion transport. Some found PAH transport to decrease almost totally using either ouabain or sodium-free bathing solutions (3)(4)(5)(24)(25)(26)(27)(28). In the present study we consistently found a submaximal inhibition ofJindo by directly or indirectly removing the sodium gradient.…”
Section: Methodssupporting
confidence: 84%
See 1 more Smart Citation
“…Many studies in different species, using different experimental techniques and designs, have addressed the sodium dependency ofthis active basolateral anion transport. Some found PAH transport to decrease almost totally using either ouabain or sodium-free bathing solutions (3)(4)(5)(24)(25)(26)(27)(28). In the present study we consistently found a submaximal inhibition ofJindo by directly or indirectly removing the sodium gradient.…”
Section: Methodssupporting
confidence: 84%
“…The latter include numerous drugs. There is general agreement that the site of action of organic anion secretion is predominantly the proximal straight renal tubule, in particular the S2 segment (3). In contrast, the mechanism of secretion is much debated.…”
Section: Introductionmentioning
confidence: 99%
“…The mean length of the S3 segments was 1.35±0.01 mm (n = 20) in length and therefore some tubules extended into the medullary rays from the outer stripe of the outer medulla, which is -1 mm in thickness. In a previous electron micrographic study of the rabbit proximal tubule, S3 cells were found chiefly in the innermost regions of the cortex and the outer stripe of the outer medulla (37). A large luminal disequilibrium pH was consistently detected independent of which end of the tubule was attached to the collection pipette indicating that the part ofthe proximal straight tubule that lacks carbonic anhydrase is more extensive than just the outer medullary portion of the proximal straight tubule.…”
Section: Resultsmentioning
confidence: 76%
“…Ouabain did not affect volume reabsorption in SFPCT under condition INTRODUCTION As evidenced by two recent reviews (1, 2) the subject of structural and functional heterogeneity ofnephrons has become a major interest of many investigators of renal physiology. Stimulated by earlier studies documenting anatomical differences between nephrons originating in the superficial and deep cortex (3)(4)(5), recent studies have been aimed at determining whether functional counterparts ofthese anatomic differences exist (6)(7)(8)(9)(10). In a previous in vitro microperfusion study (7) significant intrinsic functional differences were found to exist both between proximal convoluted tubule segments from superficial and juxtamedullary nephrons and between early and later segments of superficial convolutions.…”
mentioning
confidence: 99%